The Dutch legacy : radical thinkers of the 17th century and the Enlightenment - Lavaert, Sonja, 1958- (Religious Studies, Theology and Philosophy E-Books Online, Collection 2016, ISBN: 9789004303942., 2016)
While Spinoza's impact on the early Enlightenment has always found due attention of historians of philosophy, several 17th-century Dutch thinkers who were active before Spinoza's Tractatus theologico-politicus was published have been largely neglected: in particular Spinoza's teacher, Franciscus van den Enden ( Vrye Politijke Stellingen , 1665), Johan and Pieter de la Court ( Consideratien van Staet , 1660, Politike discoursen , 1662), Lodewijk Meyer ( Philosophia S. Scripturae Interpres , 1666), the anonymous De Jure Ecclesiasticorum (1665), and Adriaan Koerbagh ( Een Bloemhof van allerley lieflijkheyd , 1668, Een Ligt schynende in duystere plaatsen , 1668). The articles of this volume focus on their political philosophy as well as their philosophy of religion in order to assess their contributions to the development of radical movements (republicanism / anti-monarchism, critique of religion, atheism) in the Enlightenment.